Feeding habits and their implications for the conservation of the endangered semiaquatic frog Atelognathus patagonicus (Anura, Neobatrachia) in a northwestern Patagonian pond - Cuello, María Elena; Bello, María Teresa; Kun, Marcelo; Úbeda, Carmen A. (Phyllomedusa: Journal of Herpetology, 2006)
Feeding habits and their implications for the conservation of the endangered semiaquatic frog Atelognathus patagonicus (Anura, Neobatrachia) in a northwestern Patagonian pond. Atelognathus patagonicus (Gallardo, 1962) is an endemic frog species whose distribution is restricted to an endorheic pond system in basaltic basins in the northwest of the Argentinean Patagonia. Atelognathus patagonicus has two morphotypes: aquatic and littoral. This study presents data on the diet of A. patagonicus in Laguna del Burro, in Neuquén Province. Digestive tracts were analyzed for 20 specimens: 17 of the aquatic form and 3 of the littoral form. Diversity and trophic niche breadth, and index of relative importance (IRI) were calculated for the aquatic form. Nine food categories were found in the stomachs and intestine with the most important being Odonate naiads (Rhionaeschna sp.; IRI% = 86.57) and amphipod crustaceans (Hyalella sp.; IRI% = 12.89). There was not a statistically significant correlation between snout-vent length and mouth width of the frogs and mean prey lengths. For the littoral form of A. patagonicus, 25 prey categories were found, and all preys were adult terrestrial arthropods. Conclusions about the feeding habits of Atelognathus patagonicus and their implications for the design of conservation programs for the species are also given.